BS ISO 6980-3. Nuclear energy. Reference beta-particle radiation. Part 3. Calibration of area and personal dosemeters and the determination of their response as a function of beta radiation energy and angle of incidence (2nd February 2022) - British Standards Institution,
No abstract available